Seismic vulnerability assessment of old churches in the twin cities of Bhubaneswar and Cuttack using the macroelemental approach - Mishra, Mayank; Puneeth, Rabilli; Ramana, G. V. (Frontiers in Built Environment, 2022)
Historic buildings are the cultural and traditional identity of a country. However, these buildings are vulnerable to earthquakes because of their aged structure, poor maintenance, and inadequate structural health monitoring. Therefore, seismic vulnerability assessment is a critical aspect in the restoration and retrofitting of heritage buildings. In this study, a comprehensive survey was performed to collect the data of old and historic church buildings in and around the twin cities of Bhubaneswar and Cuttack in Odisha to evaluate the performance of these structures against seismic activity. The macroelemental method for seismic vulnerability assessment was used to calculate the seismic vulnerability index of church buildings. The probable damage was estimated based on the obtained values of the mean damage grade according to the EMS-98 scale and were compared with the grade of damageability acquired using the rapid visual screening method for Indian conditions. Damage probability matrices were constructed to determine the probabilistic future damage. This study identified church buildings that require immediate renovation and retrofitting.